Model Problem Based Learning Berbasis Media Sosial : Inovasi Pembelajaran untuk Penanaman Nilai-Nilai Islami - Rinda Dewi Afifah; Wiwin Luqna Hunaida; Abd. Muqit (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The social media-based Problem Based Learning (PBL) model is an innovative approach in Islamic Religious Education (PAI) learning that utilizes digital platforms to build more interesting and relevant learning interactions. This study aims to examine the extent of the effectiveness of this model in improving students' understanding of Islamic values, such as morals, ethics, and morals. By using social media, students are invited to discuss and solve problems related to current issues, making the learning process more contextual and experience-based. This research was conducted by literature study method, analyzing various literature related to the implementation of the PBL model, the use of social media in education, and its role in the formation of Islamic character. The results of the study show that this model is able to increase students' involvement in learning and deepen their appreciation of Islamic values through active interaction and critical reflection. However, the implementation of this model is inseparable from challenges such as disruption from irrelevant content, lack of digital literacy, and limited access to technology. To overcome this, good social media management, supervision of student activities, and improvement of digital infrastructure in schools are needed. With the right approach, the social media-based PBL model has the potential to be an effective strategy in building students' Islamic character in the digital era.